Cabaret as new journalism - Coenie de Villiers (Communicare)
In this paper the author attempts to extrapolate Bouwer's argument (Bouwer:1990) of cabanet as alternative discourse even further, and seeks to construct an exploratory argument that a measure of cabaret texts may be sufficiently journalistic In style and structure to be con sidered so-called New Journalism. The author seeks a common ground between cabaret and New Journalism by defining and tracing the his torical development of both phe nomena. Signs of Intertextuality are Identified and certain stylistic and structural elements of New Journal Ism are then operationalised In an exploratory and cursory Intertextual reading of selected South African cabaret texts. The paper does not postulate a rigid theoretical framework, but alms to stimulate further discourse and re search on the proposed Intertextual reading between cabaret and New Journalism.